2012
DOI: 10.1242/jeb.063628
|View full text |Cite
|
Sign up to set email alerts
|

Transient Ca2+ mobilization caused by osmotic shock initiates salmonid fish sperm motility

Abstract: Hayashi et al., 1987;Inaba et al., 1998). However, Morita and colleagues (Morita el al., 2005) reported that treatment of sperm with a 10% glycerol solution, before subsequent dilution into a low-osmotic solution, induced the , using fluo-4, revealed that intracellular Ca 2+ increased when sperm were suspended in hypertonic solutions, and a subsequent dilution into a hypotonic solution led to a decrease in intracellular Ca 2+ concomitant with motility initiation. In addition, upon dilution of sperm into a hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 36 publications
0
27
0
1
Order By: Relevance
“…In teleost spermatozoa, the increase of [Ca 2+ ] i can be caused by external influx via Ca 2+ channels, Ca 2+ pumps or Na + /Ca 2+ exchangers [33,[39][40][41][42], as a consequence of the activation of stretchactivated channels that can transport Ca 2+ together with K + or activate Ca 2+ channels [6,7,43,44], or by the release of Ca 2+ from intracellular stores [43,[45][46][47]. A previous study reported that the spermatozoa of gilthead seabream and striped seabream (Lithognathus mormyrus) can be activated in non-ionic solutions and that several K + and Ca 2+ channel blockers have no effect on the initiation of sperm motility in SW, suggesting that neither external K + nor Ca 2+ play a significant role [25].…”
Section: Discussionmentioning
confidence: 99%
“…In teleost spermatozoa, the increase of [Ca 2+ ] i can be caused by external influx via Ca 2+ channels, Ca 2+ pumps or Na + /Ca 2+ exchangers [33,[39][40][41][42], as a consequence of the activation of stretchactivated channels that can transport Ca 2+ together with K + or activate Ca 2+ channels [6,7,43,44], or by the release of Ca 2+ from intracellular stores [43,[45][46][47]. A previous study reported that the spermatozoa of gilthead seabream and striped seabream (Lithognathus mormyrus) can be activated in non-ionic solutions and that several K + and Ca 2+ channel blockers have no effect on the initiation of sperm motility in SW, suggesting that neither external K + nor Ca 2+ play a significant role [25].…”
Section: Discussionmentioning
confidence: 99%
“…17 Notably, the Ca 2+ -signaling experienced by the sperm cells is variable and this variability often correlates with species differences, morphology of the sperm cells and the environment where the sperms are released. 4,18 Recently, a number of studies have demonstrated that Transient Receptor Potential (TRP) family of channels present in neurons can conduct Ca 2+ influx in response to different physical factors such as temperature, osmotic pressure, pH and light. 19 In addition, these channels can detect a battery of signaling molecules and thus contribute to the chemosensory processes relevant for neuronal guidance and contact formation.…”
Section: Introductionmentioning
confidence: 99%
“…139,140) Since the motility initiation is tightly associated with the transient increase of intracellular Ca 2+ concentration, it is plausible that a Ca 2+ -dependent mechanism might be common to the motility activation in teleost sperm.…”
Section: Initiation and Activation Of Movementmentioning
confidence: 99%